Strategi Komunikasi Organisasi Persaudaraan Setia Hati Terate Komisariat Padepokan Madiun dalam Meningkatkan Citra Positif - Ika Wahyu Ardianti; Maria Magdalena Widiantari; Zulin Nurchayati (Lembaga Penelitian dan Pendidikan (LPP) Kalibra, 2026)
Within local culture-based institutions like Persaudaraan Setia Hati Terate (PSHT), organizational communication is vital for shaping public perception. This study explores how PSHT Komisariat Padepokan Madiun utilizes the SMCRE (Source, Message, Channel, Receiver, and Effect) framework to strengthen its community reputation. Adopting a descriptive qualitative method, data were gathered through extensive interviews, field observations, and documentary reviews. Five key informants including the branch committee head, secretary, treasurer, instructor, and a local resident representative were chosen via purposive sampling. To maintain data integrity, the study cross-verified findings using source and method triangulation, followed by data reduction, layout formatting, and final synthesis. The analysis reveals that the organization’s positive standing relies on four pillars: the trustworthiness of its leadership as information sources, core messaging centered on moral growth and brotherhood, a hybrid approach of face-to-face and digital outreach, and hands-on civic engagement. Ultimately, the paper concludes that a well-rounded communication approach successfully reshapes how the public views PSHT-elevating its identity from a standard martial arts club to a prominent hub for character building and community service.